Comprehensive Immunopeptidome Analysis of I-Ab-bound peptides from Thymus, Splenic B cells and Dendritic cells in C57BL/6 mice. (October 2022) - Nanaware, Padma; Calvo-Calle, Mauricio; Lu, Liying; Jurewicz, Mollie; Santambrogio, Laura; Stern, Lawrence
Abstract : Antigen presentation in the thymus is central to selection of CD4+ and CD8+ T cells. Despite postulated roles for differential central and peripheral antigen presentation pathways for MHC-I and MHC-II, comprehensive MHC Class II immunopeptidome analysis of the thymus has not been reported. Advances in mass spectrometry (MS) technology now allow analysis of the MHC-presented peptidomes of tissue samples containing small numbers of antigen-presenting cells. To map the immunopeptidome in the thymus of C57/BL6 mice presented by I-Ab, we used immunoaffinity coupled to MS. We identified >1000 peptides using a conventional data-dependent acquisition strategy (DDA). We compared the immunopeptidome of thymus to that of the splenic B cells and dendritic cells. We also identified >1000 peptides in splenic B cells and dendritic cells. Some of the core epitopes were unique to thymus or splenic B cells or dendritic cells, although most were shared. We observed differences in the general characteristics of the peptidomes presented by thymus as compared to splenic B cells and dendritic cells, including length distribution and hydrophobicity. To help understand the differences, we selected 57 peptides representative of thymic-derived, splenic B-derived, or shared peptidomes, and studied their binding affinity to I-Ab. Results suggest that the pool of peptides presented by I-Ab in thymus has lower MHC binding affinities than does the pool presented by splenic B cells. We are further mapping the immunopeptidome of mTEC's to understand the peptide length differences in thymus peptidome and if they are regulated by differential DM mediated editing. We are also exploring a data-independent acquisition strategy (DIA) for quantitative comparison of peptides identified in thymus, splenic B cells and dendritic cells to further characterize antigen presentation differences in thymus and periphery.